The role of hexokinase in cardioprotection – mechanism and potential for translation - Halestrap, Andrew P (Br J Pharmacol, 2015)
Mitochondrial permeability transition pore (mPTP) opening plays a critical role in cardiac reperfusion injury and its prevention is cardioprotective. Tumour cell mitochondria usually have high levels of hexokinase isoform 2 (HK2) bound to their outer mitochondrial membranes (OMM) and HK2 binding to heart mitochondria has also been implicated in resistance to reperfusion injury. HK2 dissociates from heart mitochondria during ischaemia, and the extent of this correlates with the infarct size on reperfusion. Here we review the mechanisms and regulations of HK2 binding to mitochondria and how this inhibits mPTP opening and consequent reperfusion injury. Major determinants of HK2 dissociation are the elevated glucose‐6‐phosphate concentrations and decreased pH in ischaemia. These are modulated by the myriad of signalling pathways implicated in preconditioning protocols as a result of a decrease in pre‐ischaemic glycogen content. Loss of mitochondrial HK2 during ischaemia is associated with permeabilization of the OMM to cytochrome c, which leads to greater reactive oxygen species production and mPTP opening during reperfusion. Potential interactions between HK2 and OMM proteins associated with mitochondrial fission (e.g. Drp1) and apoptosis (B‐cell lymphoma 2 family members) in these processes are examined. Also considered is the role of HK2 binding in stabilizing contact sites between the OMM and the inner membrane. Breakage of these during ischaemia is proposed to facilitate cytochrome c loss during ischaemia while increasing mPTP opening and compromising cellular bioenergetics during reperfusion. We end by highlighting the many unanswered questions and discussing the potential of modulating mitochondrial HK2 binding as a pharmacological target. LINKED ARTICLES: This article is part of a themed section on Conditioning the Heart – Pathways to Translation. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2015.172.issue‐8